.5(6x+8)=1.1-(x-3)

Simple and best practice solution for .5(6x+8)=1.1-(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .5(6x+8)=1.1-(x-3) equation:


Simplifying
0.5(6x + 8) = 1.1 + -1(x + -3)

Reorder the terms:
0.5(8 + 6x) = 1.1 + -1(x + -3)
(8 * 0.5 + 6x * 0.5) = 1.1 + -1(x + -3)
(4 + 3x) = 1.1 + -1(x + -3)

Reorder the terms:
4 + 3x = 1.1 + -1(-3 + x)
4 + 3x = 1.1 + (-3 * -1 + x * -1)
4 + 3x = 1.1 + (3 + -1x)

Combine like terms: 1.1 + 3 = 4.1
4 + 3x = 4.1 + -1x

Solving
4 + 3x = 4.1 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
4 + 3x + x = 4.1 + -1x + x

Combine like terms: 3x + x = 4x
4 + 4x = 4.1 + -1x + x

Combine like terms: -1x + x = 0
4 + 4x = 4.1 + 0
4 + 4x = 4.1

Add '-4' to each side of the equation.
4 + -4 + 4x = 4.1 + -4

Combine like terms: 4 + -4 = 0
0 + 4x = 4.1 + -4
4x = 4.1 + -4

Combine like terms: 4.1 + -4 = 0.1
4x = 0.1

Divide each side by '4'.
x = 0.025

Simplifying
x = 0.025

See similar equations:

| -6x^2+21x-15=0 | | .44(z-18)-30=6 | | 0.9x-2.6=0.1 | | 8x-2x+5=x-8+13 | | 12(p+6)= | | 16/p-3q | | 2(x-3x+4)=0 | | -t=13 | | y+9=-7(x-5) | | 0=x^2+11x-28 | | 5x-5/3=-6/5x-7/5 | | -42x^2+15x+18=0 | | 1/2v-2/7=-1/5 | | 1/2(x-2)=1 | | 1000.00+5000.00x=1200.00 | | 34*14x=78 | | 9x-1=9(x-9) | | 1.041(3/x)=1 | | -4x^2-22x-24=0 | | 3/7w-1/2=-4/3 | | 7+2lnx=5 | | 5m+7=67 | | 3z+7=6z-7(2-6z) | | 4x+3=4(4)+3 | | 6(4x+3)=24x+18 | | 56=-7z | | -7/4x=-49 | | -0.75x+y=-12 | | S-3s/8=5/8 | | 3x/8=9/2x | | 11x+3=13x-9 | | X^2+0x-121=0 |

Equations solver categories